Effects of Rio de Janeiro Ar Livre program on the autonomy of octogenarian elderly women - Aguirres, Larissa (2018)
With the increase in life expectancy, it is important to acknowledge the impact of health promotion programs on the elderly. The aimed of this study was to evaluate the influence of the Rio de Janeiro Ar Livre physical program on the functional autonomy of octogenarian elderly women´s. To this end, elderly women´s from 19 Rio de Janeiro Ar Livre program gyms were selected for the experimental group (EG) (n=23; 82.57±3.78 years), and for the Control Group (CG) (n=17; 82.88±2.23 years) from the attending cohabitation houses of the City of Rio de Janeiro. To access the functional autonomy was used Rikli and Jones (1999) protocol in two times separated by (28 weeks). It was observed in the EG a significant (p=0.010) increase in Upper limbs' strength test (13.00±3.41 to 15.09±3.60 times, pre and post innervation, respectively) and a significant (p=0.002) increase in 2 minutes Step test in the CG (36.59±15.00 to 47.24±10.96 times, pre and post, respectively). However, any significant differences between groups were observed in all variables analysed. Based in the present data we can conclude that the training program was only effective in the promotions of the functional strength of the upper limbs and to maintain the functional autonomy of octogenarian elderly women.